A global tax on interest income? Exemptions for foreign investors distort markets - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2004)
Liberalization of international capital transactions has increased the options available to investors. Today the local bank is no longer the only place to keep money; savers can choose between a wealth of options in international financial markets. One side-effect of the internationalization of capital flows has frequently been tax evasion, where interest income is often not reported to the tax authorities at home. The European Union responded to this development in June 2004 by issuing a directive on EU-wide taxation of interest income. This model could be applied globally. It would make tax evasion more difficult, strengthen the financial markets in newly industrializing countries, and open up a new source of funding for development projects. (SWP Comments / SWP)
Keywords: 320